Pornography Craving, Loneliness and Body Shape Concerns among Young Adults - Priyanka; Bothra, Chakita (International Journal of Psychosocial Rehabilitation, 2020)
The current expansion of technology, namely the internet service, has greatly contributed to the increase of available pornography material (Cooper, 2009). This increase in material has eventually given rise to platform to a lot of issues. This study focuses to study the relation of individuals reported pornography craving with loneliness and body shape. Data was collected from a sample of 98 random participants, who filled out an online questionnaire. Measures included were pornography craving questionnaire, UCLA loneliness scale and body shaping questionnaire. Statistical analysis used were Pearson correlation and regression analysis. Results from analysis revealed significant and positive relation of pornography craving with loneliness and body shape concerns and results of the regression analysis reflected role of pornography craving in body shape concerns and role of body shape concerns is loneliness among young adults.